Politeness Strategy on Sympathy Expression in Domestic Violence Cases in Tiktok: A Sociopragmatic Study - Nurul Na'imahtul Rahma; I Dewa Putu Wijana (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Recently, Tiktok has been widely used by netizens to express sympathy to each other, especially on unpleasant event. This research is based on how people interact in Tiktok regarding domestic abuse happenstance. This study aims to describe the politeness strategies used to express sympathy speech in the video of a domestic violence case on TikTok and the social factors influencing politeness strategies. This type of research is descriptive qualitative. The data source comes from a Tiktok video with the account name @ilham. art59, containing news videos related to domestic violence experienced by a woman named S (initials) located in Makassar. There were 30 data samples of expressions of sympathy taken from screenshots in the Tiktok video comment section. This study uses the theoretical approach of Brown & Levinson's politeness strategy and sociopragmatic theory. The results show that the expression of sympathy in the video of domestic violence cases on Tiktok uses two politeness strategies: positive politeness and off-record. There are 6 forms of positive politeness strategies: sharing life experiences, encouraging, giving prayers, expressing sorrow, advising, and appreciating. People tend to use positive politeness strategies more than off-record strategies in expressing sympathy for victims of domestic violence. Three social factors influence politeness strategies: the situation and context of the event that triggers sympathy, the close relationship between netizens and victims of domestic violence, and collective community interaction. The research provides insights into social interactions on social media, particularly in expressing sympathy, and contributes to sociopragmatics studies.